Hadith #2294 - Sunan al-Nasa'i - Azhar bin al-Qasim al-Rasby أزهر بن القاسم الراسبي; Hamza bin 'Amr al-Aslami; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Rafa'i محمد بن رافع; Qatada قتادة; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث (Sunan al-Nasa'i)
the Messenger of Allah fasted while traveling until he reached Qudaid, then he called for a cup of milk and drank and broke his fast; he and his Companions.
Grade:

Hadith #1205 - Sunan Ibn Majah - Abu Hurairah; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Azhar bin al-Qasim al-Rasby أزهر بن القاسم الراسبي; Bakr bin Khlf al-Basri بكر بن خلف البصري; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Zakaria bin Ishaq al-Makki زكريا بن إسحاق المكي (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) was shrouded in three garments: The shirt in which he died, and a Najrani Hullah.
Grade: